Pengaruh Media Edukasi Berbasis Video terhadap Tingkat Pengetahuan Remaja Mengenai Kesehatan Reproduksi di SMA Muhammadiyah Pontianak - Natasya Tanjaya; Riska Ismawati Hakim; Dian Monalisa Rusliani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Background: The urgency of adolescent reproductive health problems that have not been resolved is cases of unwanted pregnancies (Dr.Fitriana, 2023). Based on a preliminary study conducted for approximately 1 week, it was found at the Paris 2 Community Health Center that pregnancy cases increased by as much as 29% of young women in Pontianak City experienced symptoms of blood deficiency or anemia. According to the Head of the Pontianak City Department of Health (Dinkes), Saptiko, suffering from anemia will have an impact on the pregnancy readiness of young women, after conducting a data survey, the highest number of teenagers experiencing anemia was at Muhammadiyah 1 High School, Pontianak City. Research Method: The research design is Pre-Experimental Design with One Group Pretest-Posttest Control group design. The research sample consists of 78 people who will be given video educational media. The instrument used in the research was a knowledge questionnaire about reproductive health. The sampling technique used was simple random sampling. Analysis uses t test with α ≤ 0.05. Research Results: The results of this research obtained an average knowledge before 70.39 and after 86.73. The results of increasing knowledge before and after are 16.34. The Wilcoxon test results obtained p value = 0.000 < 0.05. Conclusion: There is a difference in the provision of video-based educational media on the level of knowledge of adolescents regarding reproductive health at SMA Muhammadiyah Pontianak.